Action of naftopidil on spinal serotonergic neurotransmission for inhibition of the micturition reflex in rats. Issue 3 (29th April 2016) - Sugaya, Kimio; Nishijima, Saori; Kadekawa, Katsumi; Ashitomi, Katsuhiro; Ueda, Tomoyuki; Yamamoto, Hideyuki; Hattori, Tsuyoshi
Abstract : Aims: We examined the mechanism of action of naftopidil, an α1D/A blocker, on spinal descending serotonergic neurotransmission for the micturition reflex. Methods: We examined (1) urinary 5‐hydroxyindole acetic acid (5‐HIAA) after intraperitoneal administration of saline, para‐chlorophenylalanine (PCPA; a serotonin synthetic enzyme inhibitor), and/or 5‐hydroxytryptophan (5‐HTP; a serotonin precursor); (2) isovolumetric cystometry after intraperitoneal administration of saline, PCPA, and/or 5‐HTP and intravenous injection of naftopidil; and (3) isovolumetric cystometry before and after intrathecal administration of serotonin (5‐HT) receptor antagonists and intravenous injection of naftopidil. Results: PCPA decreased and 5‐HTP increased urinary 5‐HIAA/creatinine. Intraperitoneal injection of PCPA did not influence cystometric parameters. Intraperitoneal injection of 5‐HTP significantly shortened the interval between bladder contractions. Intravenous injection of naftopidil transiently abolished bladder contractions. However, the duration of abolishment of bladder contractions after injection of naftopidil in rats given PCPA was significantly shorter than that in rats given vehicle, but significantly longer than that in rats given PCPA and 5‐HTP. Intrathecal injection of 5‐HT1B, 5‐HT3, or 5‐HT7 receptor antagonists significantly prolonged the interval between bladder contractions. Intrathecal injection of 5‐HT1D or 5‐HT2B receptor antagonists significantly shortened the interval between bladder contractions. Combined administration of the maximum non‐effective dose of 5‐HT1D, 5‐HT2A, 5‐HT2B, 5‐HT2C, or 5‐HT3 receptor antagonists and intravenous injection of naftopidil significantly shortened the duration of abolishment of bladder contraction compared to intravenous injection of naftopidil alone. Conclusions: Naftopidil may inhibit the micturition reflex via 5‐HT1D, 5‐HT2A, 5‐HT2B, 5‐HT2C, and 5‐HT3 receptors in the spinal cord. Neurourol. Urodynam. 36:604–609, 2017 . © 2016 Wiley Periodicals, Inc.